Electrical characterization of cells with Conductive Atomic Force Microscopy - Bolaños Torres, Erick Joniher (2024)
Electrical activity plays a vital role in various cellular functions, including signal conduction, muscle contraction, action potentials, and nutrient transport. Investigating these activities poses significant challenges due to the complexity of cellular mechanisms. However, studying the intrinsic electrical properties of cells can provide valuable insights into their state and type, enabling the analysis of variations under pathological conditions and pharmacological treatments. This thesis presents an analysis of the electrical conductivity of cells from two different lineages, OFCOL II and L929, facilitating the study of charge transport mechanisms in different cellular regions and their relation to various biological functions. Conductive Atomic Force Microscopy (C-AFM) was employed to measure the electrical conductivity of these cell lines. The study involved using current distribution images and current-voltage (IV) curves to explore the charge transport mechanism across different cellular regions. Theoretical models were applied to these measurements to gain a deeper understanding of how charge propagates through the cells. AFM provides high-resolution images and quantifies properties such as viscoelasticity and stiffness. Beyond mechanical properties, its variant, C-AFM, has been utilized to measure electrical properties in metals, oxides, semiconductors, and biological samples. To minimize interference, the cells were fixed and cultured on a transparent conductive substrate. This approach enabled detailed and accurate measurements of the electrical properties of the cells, offering new insights into cellular function and behavior.